Leveraging cultural wealth: an appreciative inquiry into the success of community college student parents - Cook, Channell Lynn (My University, 2026)
Student parents comprise approximately 18% of all undergraduates in the United States, with about 51% enrolled in community colleges (Anderson et al., 2024). National data reveal significant disparities in educational attainment between college students who are parents and those who are not. Reichlin Cruse et al. (2019) reported that only 37% of student parents completed a degree or certificate within six years, compared to 59% of students without children. This qualitative study examined how successful community college student parents utilized their cultural wealth and effectively integrated personal, community, and institutional resources to balance their academic and parenting responsibilities. Guided by Appreciative Inquiry theory and Yosso’s (2005) Community Cultural Wealth (CCW), the research examined how student parents utilized aspirational, linguistic, familial, social, navigational, and resistant capital to support persistence and achievement in higher education. It also explored what works in terms of institutional support systems and services to promote student parent success. Semi-structured interviews were conducted with 12 female participants attending a mid-sized Hispanic-Serving Institution in the greater Houston, Texas area. All participants had completed at least 45 college credit hours, earned a certificate or degree, or transitioned into a career related to their field of study. Eleven identified as first-generation college students, representing varied family structures, employment statuses, and parenting circumstances. Findings indicated that participants actively employed all six forms of cultural capital, often in overlapping and mutually reinforcing ways. Aspirational capital reflected their determination to create intergenerational change and serve as educational role models for their children. Familial capital was expressed through emotional, logistical, and motivational support from children, partners, and extended families. Social capital emerged from peer, mentor, and faith-based networks. Navigational capital involved self-advocacy, strategic organization, and effective utilization of institutional resources. Resistant capital was evident in participants’ rejection of deficit narratives and commitment to breaking cycles of limited educational attainment. Linguistic capital supported effective communication and cultural adaptability. Institutional supports played a pivotal role in persistence, with childcare assistance identified as the most essential infrastructure. Other key supports included basic needs services, TRiO Student Support Services, academic assistance, and positive relationships with faculty and staff. However, awareness of available resources varied, underscoring the need for proactive and systematic communication. Two additional themes emerged during the study: time as a critical resource and parenting as a source of transferable skills and motivation. Participants’ strategic time management and the organizational, multitasking, and resilience skills developed through parenting directly contributed to academic success. The study's implications emphasize that student-parent success depends on the interaction between students' inherent cultural wealth and institutional recognition of these strengths. Community colleges can enhance outcomes by treating childcare as essential infrastructure, strengthening outreach about resources, designing flexible and family-friendly environments, and fostering cultural responsiveness among faculty and staff. Policymakers should prioritize funding for childcare, basic needs, and comprehensive student services while including student-parent perspectives in program development and evaluation. Overall, this research challenged deficit-based narratives by demonstrating that student-parent success arises not solely from individual determination but from a reciprocal process in which cultural wealth and institutional support systems reinforce one another, advancing equity, inclusion, and opportunity in higher education.
Keywords: Student parent success; Community college; Community cultural wealth; Appreciative inquiry; Academic persistance; Basic need support